Preliminary study of selected drinking water samples in Mexico City - Alfonso Lugo (Revista Internacional de Contaminación Ambiental, 1997)
Mexico City is a critica1 example of drinking water supply and pollution, dueto its population of nineteenmillion within a closed basin, 2300 m above sea level. The increasing urbanization has diminished the rateof aquifer reload, and a large amount of water is brought fiom lower and more distant zones, with increasedenergetic and ecological costs. To obtain data about drinking water at selected points in the city, 63locations were sampled from April to Deceniber in 1989 (209 total samples). Where available, sampleswere taken from municipal network intakes, cistems, roof tanks and kitchen tap water. At least onelocation was tested in 24 ofthe 27 Municipal Districts in tlie city. Measured pliysico-cliemical parameterswere: temperature, pH, alkalinity, hardness, chloride, sulfate, silica, total solids, suspended solids andconductivity (K,,). Biological analysis were total and faecal coliforms, and faecal streptococci. Based onprincipal component analysis ordination, data were arranged into six groups of water quality. Drinkingwater quality at the municipal network intakes was good in 53% of the cases, although pollution wasdetected when water was distributed by tank tmcks, when it carne from local wells in-the State of Mexico,or when water had a high suspended solids content. Drinking water was often polluted inside tlie housesdue to poor domestic handling.